Keterlibatan Gereja Dalam Membangun Nilai-Nilai Kesusilaan Di Tengah Masyarakat Majemuk - Yohana Letek Lamak; Instansakti Pius X (Jurnal Teologi Injili dan Pendidikan Agama, 2024)
The involvement of the church in building moral values in a pluralistic society is important. This is because the church has an important role in shaping the character and morality of society. This research aims to examine the church's involvement in building moral values in a pluralistic society. The research method used is a literature study about churches and pluralistic societies. This research also shows that the church is involved in building moral values in a pluralistic society through various programs and activities, such as religious education and social services. These programs and activities aim to instill Christian moral values, such as love, forgiveness and justice. Church involvement in this matter can be a positive contribution in creating a better society. This research can also have positive implications for the church, society and government. For the church, this research can be a motivation to increase its involvement in building moral values in a pluralistic society. For the public, the results of this research can provide an understanding of the role of the church in building moral values. For the government, the results of this research can be a reference in developing policies that support the church's efforts to build moral values.